Validation calculations of hemodynamic problems using the FlowVision software package in parallel mode - Kalugina, Maria D.; Kashirin, Vladimir S.; Lobanov, Alexey I. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2023)
The calculations of the test problem associated with the simulation of the flow in an idealized medical device were carried out in the FlowVision software package. The calculations were carried out for laminar, turbulent and transitional flow regimes. The scalability of the problem is studied. Based on the solution of the test problem, a conclusion was made about the possibility of using the FlowVision software package to solve hemodynamic problems.